Ethno-Medicinal Perspectives of Antidiabetic Plants from Sikkim-Himalaya: An Integrative Updated Review - Bhutia, Chowang Narbu; Sharma, Anurag; Bhutia, Pempo Lhamu; Manger, Roshan; Chettri, Prashant; Gurung, Anuj; Bhutia, Sonam (Journal of Pharmacy Practice and Community Medicine, 2026)
Sikkim state is considered as one of the hot spots in the northeast state of India. Talking to the richness of the biodiversity, there are about 490 medicinal plants were recorded only in Sikkim Himalaya till now. Traditional healers select these herbal remedies based on appropriate disease indications and symptoms. It is the precise time to compile Sikkim’s traditional medicine documentation process for future use. A thorough literature search was conducted to gather the data, and reputable web resources like PubMed, ScienceDirect, ResearchGate, Google Scholar, Core, and 1library were consulted. In the first stage, we used broad keywords related to “ANTI-DIABETIC,” followed by targeted searches for plants that are found in Sikkim-India. The review process only covered papers published in the recent 35 years, beginning in the 1990s. We employed Boolean operators like “AND,” “OR,” and “NOT” to narrow down our search results. In this review paper, we have highlighted 62 antidiabetic medicinal plants belonging to 36 families for the first time in a single work with their botanical name, family, local name, parts used, intake process, geographical distribution throughout the world, possible Mechanism of Action (MOA) and their ethno-medicinal utilities Sikkim Himalaya. In Figure 1, we have highlighted the family wise distribution and the part used. Based on the family wise use, it was found that Asteraceae are in higher use (8%) and followed by Solanaceae, Fabaceae Rutaceae and Caesalpiniaceae (5%) and Asparagaceae, Zingiberaceae, Menispermanceae, Gentianaceae Urticaceae and Caesalpiniaceae (3%). On other hand, in case of part used, highest was leaves and root (38 and 27%). Documentation of such knowledge will definitely encourage up-coming generations to discover novel pharmaceuticals to manage the diabetic condition in the future.
Keywords: Antidiabetic; Medicinal plants; Natural medicines; Sikkim Himalaya; Updated traditional insights